A responsabilidade civil objetiva como mecanismo de concretização dos direitos fundamentais no âmbito das relações privadas - COSTA, Élida de Cássia Mamede da (Universidade Federal do Pará, 2017)
This work proposes to accent the objective civil responsibility based in risk theory as a way to perform fundamentals rights / human rights / personality rights in privates juridical relations, because there was capacity to enlarge the possibility of victims of moral and materials damages be compensated without to prove or discussion about agent‟s guilt. So, disciplining society and relations presents as “risked”, this work aspires to ratify the legislative progress about this subject matter as a step to protect fundamental rights. At second, this article will show briefly the relation between civil responsibility and human dignity, always examining victims‟ situation. The present work investigates, at end, the fundamentals rights‟ efficacy in objective civil responsibility plan, searching parameters to solve the conflict between fundamental rights in privates juridical relations, showing the social sociability and the private right.